2022
DOI: 10.1155/2022/7434426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methomyl on Growth, Antioxidant System of GIFT (Oreochromis niloticus), and Residue in the Presence of Water Spinach (Ipomoea aquatica Forsk)

Abstract: This study was conducted to investigate the effect of methomyl (MET) on the growth and antioxidant system of GIFT (5.28 ± 0.12, n = 180) in the presence of water spinach (Ipomoea aquatica) aas a floating bed. Four treatment groups have been established, named control (0), 2, 20, and 200 μg/L MET. Results showed that at moderate temperatures such as 25°C to 30°C, tilapia’s feed consumption increased and body weight improved. SOD, CAT, and GSH in the liver of GIFT indicated the significant increase under MET exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Our previous studies showed water spinach reduced part of the water quality indexes in the MET (<200 µg/L) groups. 26 Remarkably, compared with a previous study, ROS-related enzymes of exposed tilapia fed on peppermint presented in the system as a floating bed were significantly normalized in low concentration (0.2 µg/L). In addition, results showed a decrease in the levels of all ROS-related enzymes in the concentration of 2.0 and 20 µg/L.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Our previous studies showed water spinach reduced part of the water quality indexes in the MET (<200 µg/L) groups. 26 Remarkably, compared with a previous study, ROS-related enzymes of exposed tilapia fed on peppermint presented in the system as a floating bed were significantly normalized in low concentration (0.2 µg/L). In addition, results showed a decrease in the levels of all ROS-related enzymes in the concentration of 2.0 and 20 µg/L.…”
Section: Discussioncontrasting
confidence: 50%
“… 37 Our study showed growing spinach with water may have a positive effect on the prevention of GIFT's liver toxic damage. 26 Astragaloside IV from the medical herb Radix astragali , revealed a protective effect against acute cerebral ischemic/reperfusion injury through a PPARγ-dependent manner, which has been taken as a promising therapeutic agent. 38 The most important thing is to find active substances that can improve the immune ability or disease resistance of fish from medical herbs, like RES in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that volatile allelochemicals had a weak antioxidative ability [5], and berberine (a kind of alkaloid extracted from plants) has been found as the main allelochemical from the root of Coptis chinensis, implementing the disease inhibitory effects [6]. However, some vegetable-like plants, like water spinach (Ipomoea aquatica forsk), which can be useful for in-situ remediation with the enhancement of water quality and the removal of pesticide simultaneously, can absorb methomyl [7], and such aquatic plants have the advantage of nutrient absorption [7]. Our recent study demonstrated that planting with mint (Mentha haplocalyx Briq) can alleviate the toxicological effects produced by methomyl, shape the intestinal microbiota in tilapia, and strengthen the connection between pond water quality and fish metabolic parameters [8].…”
Section: Introductionmentioning
confidence: 99%